Critical Review of Collaborative Approaches between Nursing and Health Administration for Improved Patient Outcomes - Al-Bahri , Hamad Mohammad S; Alyami, Mohammed Saleh N; Laslom , Hamad Soeib S; Al Amer , Nasser Mohamed H; Alyami, Mahdi Saleh N; Al-Yami , Nasser Saleh N; Alrakah , Rakan Mohammed G; Alrakah , Naif Mohammed G; Alrakah , Mahdi Mohammed A; Alyam, Faleh Saleh M; Alshahabilah , Yahya Nasser A; Al Muammar, Sami Mahdi (Journal of Ecohumanism, 2024)
Cooperation between nursing and health administration is critical to today’s healthcare organizations in order to provide the best storage of patient results. Managing the shortages of nursing staff, the effective distribution of patient load among the nurses, and ensuring that the health administrators can efficiently manage and allocate the available health resources in the healthcare organizations, these two groups of personnel must collaborate effectively. This review focuses on certain collaborative endeavors between the nursing profession and health administration, the effects of these collaborations on patients, and recommendations for stakeholder collaboration. Subsequently, acquiring a clear insight into this synergy will help different healthcare provider organizations develop policies and structures that support the synergy and improve patient care. This paper discusses variables of shared leadership, communication, and teamwork, and the difficulties and approaches to effectively collaborating are discussed.